Encyclopedias about Muslim civilisations - Khanbaghi, Aptin; Aga Khan University. Institute for the Study of Muslim Civilisations. (Edinburgh : Edinburgh University Press in association with the Aga Khan University, Institute for the Study of Muslim Civilisations)
Includes bibliographical references